Multiplexed In Vivo Imaging Using Size‐Controlled Quantum Dots in the Second Near‐Infrared Window. Issue 24 (19th November 2018) - Jeong, Sanghwa; Jung, Yebin; Bok, Seoyeon; Ryu, Yeon‐Mi; Lee, Sumin; Kim, Young‐Eun; Song, Jaejung; Kim, Miyeon; Kim, Sang‐Yeob; Ahn, G‐One; Kim, Sungjee
Abstract: PbS/CdS core/shell quantum dots (QDs) that emit at the second near‐infrared (NIR‐II, 1000–1700 nm) window are synthesized. The PbS seed size and CdS shell thicknesses are carefully controlled to produce bright and narrow fluorescence that are suitable for multiplexing. A polymer encapsulation yields polymer‐encapsulated NIR‐II QDs (PQDs), which provides the QDs with long‐term fluorescence stability over a week in biological media. Exploiting the simple bioconjugation capability of PQDs, folic acids are conjugated to PQDs that can efficiently label folate receptor overexpressing cell lines. The PQDs afford multiplexed and nearly real‐time longitudinal whole‐body in vivo imaging. Two NIR‐II QD probes are prepared: folic acid‐conjugated PQDs (FA‐PQDs) emitting at 1280 nm and unconjugated PQDs emitting at 1080 nm. The two PQDs are engineered to have compact and similar hydrodynamic sizes. A mixture of the folic acid‐conjugated PQD and unconjugated PQDs is injected intravenously into a tumor‐xenografted mouse, and the signals from them are monitored. This NIR‐II whole‐body imaging with the two PQDs provides precise evaluation of the active ligand‐assisted tumor‐targeting capability of the FA‐PQD probe because the hydrodynamic size control of the two PQDs effectively eliminates effects from the size‐dependent accumulations by permeations and retentions in tumors. Abstract : Multiplexed and longitudinal whole‐body in vivo second near‐infrared imaging is demonstrated with polymer‐encapsulated PbS/CdS quantum dots. The PbS seed, CdS shell, and surface coating are carefully controlled to produce bright and narrow fluorescence that are suitable for multiplexing. The probes afford the precise evaluation of the active tumor targetting capability of folic acid‐conjugated quantum dot probes.